Sistem Pendukung Keputusan Seleksi Data Terpadu Kesejahteraan Sosial Menggunakan Metode K-Means dan SAW - Tutus Praningki; Moyo Hady Poernomo; Ignasius Boli Suban (Universitas Budi Darma, 2023)
Indonesia as a developing country cannot be free from problems related to poverty, Some people still have income that is not sufficient for a decent life. The Indonesian government has several programs that are useful for reducing poverty, namely the Bantuan Pangan Non Tunai (BPNT) atau Program Keluarga Harapan (PKH). Often in the process of distributing aid there are obstacles or problems, the obstacle that often arises is determining the right family to receive assistance. Sub-districts or villages are at the forefront of the data collection process and selection for recommendation into the Data Terpadu Kesejahteraan Sosial (DTKS). This research aims to develop an application product that can help the Ngronggo Kediri sub-district to accurately determine which families are entitled to assistance. The K-Means and SAW methods are used to determine which families are included in the DTKS. The K-Means method is used for the clustering process and SAW is used for the weighting process. The final weight shows that the highest recommended family weight is 91,2%, and the lowest is 51.4%.